IMPLEMENTASI WORKSHEET ANGKA UNTUK PENGENALAN MATEMATIKA PERMULAAN ANAK USIA DINI - Winda Nur Ayu Afifaroh (STAINU Purworejo, 2022)
Teachers have a very important role in the learning process which includes planning, implementing, and assessing. In planning the teacher must pay attention to several aspects that must be in accordance with the child. The use of media must be appropriate to the level of child development. One of them is the use of worksheets to introduce mathematics to early childhood. In this case there must be a special event to help the learning process. So that it will make it easier for students to learn and increase knowledge for children. Stick with the concept of play, so as not to eliminate early childhood learning styles. The type of research used in this research is descriptive with a qualitative approach. This research was conducted in Juwiring Village with children aged 4-5 years as research subjects. Data collection methods include: observation and documentation. Based on the analysis it was found that teaching mathematics to children can use interesting media images, so that it makes children interested in learning to understand the material. The emergence of their own desire in children to learn and do tasks continuously. This research shows that there is an increase in students' learning motivation in early childhood by using pictures of fruits. With interesting pictures can make children feel interested in learning material. So that children's learning motivation increases. With attractive images, children are more focused on one particular task and are less easily distracted by abstract events.